Hubungan Antara Karakteristik Pasien dan Keberhasilan Pengobatan pada Pasien TB Paru dengan DM Tipe 2 di RSP Dr. H. A. Rotinsulu - Tegar Aria Yuda; Heni Muflihah; Miranti Kania Dewi (Bandung Conference Series: Medical Science, 2024)
Abstract. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (MTB). One factor that complicates treatment is the presence of comorbidities in pulmonary TB patients, including diabetes mellitus (DM). TB patients with diabetes mellitus comorbidities (TB-DM) are known to often experience treatment failure. This study aims to analyze the relationship between patient characteristics and treatment success in DM-TB patients. This study was a cross-sectional study. The study subjects were type 2 DM-TB patients at RSP Dr. H.A. Rotinsulu for the period 2022-2023. The data used is in the form of secondary data taken from the medical record of DM-TB patients at RSP Dr.H.A. Rotinsulu. The study sample was taken using purposive sampling totaling 130 people. Characteristics include age, gender, and ownership of the National Health Insurance (JKN). The final result of treatment after 6 months cured or complete is categorized as successful. The relationship of patient characteristics with treatment success was analyzed using the chi-square test. The results showed that most of the type 2 TB-DM patients at RSP Dr. H.A Rotinsulu were adults (19-60 years) as many as 84 people (71.8%), male as many as 72 people (61.5%), had JKN as many as 100 people (85.5%), and succeeded in treatment as many as 70 people (59.9%). There was a significant association between age and treatment success (p < 0.05), but no significant association between sex and JKN ownership and treatment success (p > 0.05). The conclusion of this study is that adulthood is associated with the success of DM-TB treatment. Productive age tends to have high motivation and healing spirit that can increase the success of treatment. Abstrak. Tuberkulosis (TB) merupakan penyakit infeksi menular yang disebabkan bakteri Mycobacterium tuberculosis (MTB). Salah satu faktor yang menyulitkan pengobatan adalah adanya penyakit penyerta pada pasien TB paru, diantaranya diabetes mellitus (DM). Pasien TB dengan penyakit penyerta diabetes mellitus (TB-DM) diketahui sering mengalami kegagalan pengobatan. Penelitian ini bertujuan untuk menganalisis hubungan antara karakteristik pasien dengan keberhasilan pengobatan pada pasien TB-DM. Penelitian ini merupakan studi cross sectional. Subjek penelitian adalah pasien TB-DM tipe 2 di RSP Dr. H.A. Rotinsulu periode 2022-2023. Data yang digunakan berupa data sekunder yang diambil dari rekam medik pasien TB-DM di RSP Dr.H.A. Rotinsulu.Sampel penelitian diambil menggunakan purposive sampling berjumlah 130 orang. Karakteristik meliputi usia, jenis kelamin, dan kepemilikan Jaminan Kesehatan Nasional (JKN). Hasil akhir pengobatan setelah 6 bulan sembuh atau lengkap dikategorikan berhasil. Hubungan karakteristik pasien dengan keberhasilan pengobatan dianalisis menggunakan chi-square test. Hasil penelitian menunjukkan sebagian besar pasien TB-DM tipe 2 di RSP Dr. H.A Rotinsulu berusia dewasa (19 – 60 tahun) sebanyak 84 orang (71.8%), berjenis kelamin laki-laki sebanyak 72 orang (61.5%), memiliki JKN sebanyak 100 orang (85.5%), dan berhasil dalam pengobatan sebanyak 70 orang (59.9%). Terdapat hubungan bermakna antara usia dan keberhasilan pengobatan (p < 0,05), namun tidak terdapat hubungan bermakna antara jenis kelamin dan kepemilikan JKN dengan keberhasilan pengobatan (p > 0,05). Simpulan penelitian ini adalah usia dewasa berhubungan dengan keberhasilan pengobatan TB-DM. Usia produktif cenderung memiliki motivasi dan semangat penyembuhan yang tinggi yang dapat meningkatkan keberhasilan pengobatan.